Moderating Impact of Sustainable Building Awareness on the Relationship between Sustainability Concepts Application, Sustainability Constraints, and Knowledge Level (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Stakeholders do not adopt the concept of sustainable building in the building industry. Therefore, this research aimed at study the stakeholders' level of knowledge, awareness, and constraints of building sustainability concepts and how they affect the adoption of building sustainability concepts. A quantitative research design was employed using a questionnaire. A research sample of 201 was collected via a structured questionnaire survey that was randomly selected from 420 registered professionals in northwest Nigerian. Data collected were analysed using the SPSS and WarpPLS packages. The findings show that the level of knowledge and awareness was moderate among the stakeholders. Likewise, sustainability constraints have a negative effect on the adoption of building sustainability concepts, level of knowledge has a positive effect on the adoption of building sustainability concepts; awareness of sustainability concepts has improved the effectiveness of the relationship between sustainability constraints and adoption of building sustainability concepts, and awareness of sustainability concepts improves the effectiveness of the relationship between the level of knowledge and adoption of building sustainability concepts. Therefore, there is a need for the developing nations to emphasized regular sensitization of sustainability concepts and principles so that the menace of lack of its adoption can be curtailed.